Keunggulan Kompetitif dan Sistem Produksi Usaha Ternak Sapi Potong di Kabupaten Gunung Kidul - Nandang Sundar; Sri Widodo; Masyhuri Masyhuri; Irham Irham (Jurnal Dinamika Sosial Ekonomi, 2004)
The research has been conducted to find out a competitive advantage of beef cattle farming. Data used in this research was primary data collected through survey in Gunung Kidul Regency, Province of Daerah Istimewa Yogyakarta. The location determination was conducted in purposive based on population of beef cattle. The selected location was Sub district of Karang Mojo and Semanu. Total sample was defined in quota that is 240 beef cattle farmers, each 120 beef cattle farmers in Karang Mojo and Semanu. Sample selection was taken in simple random sampling. The result suggested that (1) Factors influenced to production of beef cattle farming were breeding, dedak, forage, labour, PCR and production system of beef cattle farming, (2) PCR value has negative relationship to production of beef cattle farming, the meaning is the higher the PCR value, the lower the production of beef cattle farming, (3) Production system and management of fattening has really a higher production than breeding production system. The competitive advantage has to be special target on building and expanding domestic beef cattle development. Considering that competitive advantage being indicators was financial price, then the increase of competitive advantage must be directed over the effort to influence the financial price, both to input or output used. Another way that can be performed to increase a competitive advantage was through the use of input that has cheap financial price.Keywords: Competitive Advantage, Production system, Beef Cattle